FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PARTISIPASI MEMBAYAR PAJAK DIKALANGAN UMKM - Usmar Usmar; Yudhistira Adwimurti; Tamrin Lanori; Patricia K. Surya (Jurnal Manajemen dan Bisnis, 2022)
This study aims to explain the magnitude of the effect of socialization, tax understanding, tax awareness on taxpayer compliance based on PP 23 of 2018 on MSME actors. The sample selection was carried out using the Accidental Sampling method with an analysis unit of MSMEs in the Pasar Majestik Shopping Center, South Jakarta in the period February - August 2020, with an analysis unit of clothing traders in each block that existed and inhabited the market who were found and were willing to fill out a questionnaire. which are given. The number of samples obtained were 100 respondents which were then processed using multiple regression data analysis with SPSS tools, hypothesis testing was carried out after going through a feasibility and reliability data test. The study concludes that the factors of tax socialization, tax understanding, knowledge of taxation information systems have a positive and significant impact on taxpayer compliance in paying PP 23 of 2018 taxes on MSME actors in the Majestik Market Shopping Center Area, South Jakarta.